Contract farming in transitional economies: A stakeholder theory perspective - Vladislav Valentinov; Drini Imami; Orjon Xhoxhi (International Food and Agribusiness Management Review, 2024)
In transitional economies, contract farming is widely recognized as a means for addressing numerous market failures affecting small farmers. Reviewing the scholarship on contract farming, we show that its traditional understandings have been framed by the narratives of transaction cost economics and power dynamics. We critically evaluate these narratives and demonstrate how stakeholder theory, with its relational understanding of business, offers a more comprehensive understanding of contract farming. We argue that a stakeholder theory perspective underscores the trust-based and collaborative nature of successful contract farming arrangements. It highlights the importance of informal and moral stakeholder relationships that compensate for the limitations of weak enforcement mechanisms and inadequate legal frameworks in transitional economies. This way, a stakeholder theory perspective on contract farming highlights its strategic management and business ethics dimensions, offering valuable guidance for cultivating successful stakeholder relationships.
Keywords: D2; M1; M2; P2; Q1; 330; contract farming; power; stakeholder theory; transaction cost economics